A novel perspective approach to explore pros and cons of face mask in prevention the spread of SARS-CoV-2 and other pathogens - M.D. Faruque Ahmad; Shadma Wahab; Fakhruddin Ali Ahmad; M. Intakhab Alam; Hissana Ather; Ayesha Siddiqua; Syed Amir Ashraf; Mohammad Abu Shaphe; Mohammed Idreesh Khan; Rashid Ali Beg (Elsevier, 2021)
Corona virus disease 2019 (COVID-19) outbreak has become a severe community health threat across the world. Covid-19 is a major illness, presently there is no as such any medicine and vaccine those can claim for complete treatment. It is spreading particularly in a feeble immune people and casualties are expanding abruptly and put the health system under strain. Among the strategic measures face mask is one of the most used measures to prevent spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Wearing a face mask possibly create a false sense of security lead to decline others measures. Face mask could be risk for the people of under lying medical conditions, old age group, outdoor exercise, acute and chronic respiratory disorders and feeble innate immune. Restrictive airflow due to face mask is the main cause of retention of CO2 called hypercapnia that can lead to respiratory failure with symptoms of tachycardia, flushed skin, dizziness, papilledema, seizure and depression. According to latest updates face shield and social distancing could be better substitute of face mask.